Analisis Kualitas Susu Sapi Perah Berdasarkan Variasi Sistem Pemeliharaan di Daerah Tropis - Ahmad Zulhandi (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study aimed to analyze the quality of dairy cow milk under different rearing systems in tropical regions. The research background is based on the fact that tropical climates create unique challenges in dairy farming, such as heat stress, feed availability, and disease prevalence, which directly affect milk production and quality. The study was conducted using a comparative observational method on three rearing systems: intensive, semi-intensive, and extensive. Data were collected from 90 dairy cows divided evenly across the systems, and milk samples were analyzed for fat content, protein, lactose, total solids, and microbial counts. The results showed that milk from intensive systems had significantly higher protein and fat content, while semi-intensive systems produced milk with a more balanced nutrient profile. Extensive systems showed lower milk quality, particularly in terms of microbial contamination. The findings highlight that the choice of rearing system significantly influences milk quality in tropical conditions. The study suggests that semi-intensive systems may provide the best balance between productivity and sustainability. These results can be used as a reference for developing dairy farming strategies in tropical regions to ensure milk quality and safety.